Phospholipase A2—A Significant Bio-Active Molecule in Honeybee (Apis mellifera L.) Venom - Mara Muntean; Adrian Florea (Molecules, 2025)
Phospholipase A2 (PLA2) is a prevalent molecule in the honeybee venom. Its importance is reflected by the number of scientists focused on studying it from various points of view. This review summarises a significant amount of data concerning this fascinating substance. Firstly, the origin and occurrence of PLA2, with similarities and differences among species or populations of bees are highlighted. Next, its synthesis, post-translational processing and structural features are described, followed by the PLA2 availability. In a larger section, the multiple effects of honeybee venom PLA2 are detailed, starting with the main ability as an enzyme to interact with biological membranes and to hydrolyse the sn-2 ester bond in 1,2-diacyl-sn-3-phosphoglycerides; the docking process, the substrate binding and the catalytic steps are analysed too. Then, the pro-/anti-inflammatory effect and allergenic property, the anticoagulant effect and the involvement of PLA2 in apoptosis are revised. Selected antiviral, antibiotic and antitumoral effects of PLA2, as well as its use in immunotherapy are mentioned as beneficial applications. Additionally, the mechanisms of toxicity of PLA2 are presented in detail. Finally, a number of anti-PLA2 compounds are enumerated. In each section, the features of the honeybee venom molecule are discussed in relation to PLA2s from other species.